Intellectual disabilities. (November 2020) - Simpson, Neill; Mizen, Lindsay; Cooper, Sally-Ann
Abstract: All doctors should expect to have some patients with intellectual disabilities. People with intellectual disabilities have high rates of physical and mental ill-health, and co-morbidity is typical. Frequently associated conditions such as epilepsy, aspiration and choking can cause avoidable death, and problems such as gastroesophageal reflux disorder, sensory impairments and injuries can cause recurrent symptoms or persistent disability. Other developmental disorders, psychosis and behavioural problems are common. Some conditions related to the causes of a person's intellectual disabilities (e.g. 'behavioural phenotypes') can benefit from interventions. Be aware of readily treatable associated physical conditions such as hypothyroidism in Down syndrome. Problem behaviour can be a sign of distress, which can be the result of physical ill-health, mental ill-health, environmental factors or a combination of these. Medical assessment requires excellent communication skills and multiple sources of information, which must involve relatives and paid carers as well as the person with intellectual disabilities, so you should allocate sufficient time. Use a biopsychosocial–developmental framework. Avoid attributing symptoms of medical conditions to the person's developmental disabilities ('diagnostic overshadowing'), which results in illness remaining untreated. People with intellectual disabilities face many barriers in accessing healthcare, and proactive approaches are required. Specialist intellectual disabilities teams, where available, are excellent resources for specialist assessment and advice.